Pengaruh Latihan Daya Ledak Otot Tungkai Terhadap Ketepatan Smash Bola Voli Pada Atlet Voli Putri SSC Unpatti - Sambono, Arnold Bolanama; Unmehopa, Wehelmina; Tahapary, Jhoni Melvin (MANGGUREBE: Journal Physical Education, Health and Recreation, 2025)
Leg muscle explosive power is one of the biomotor components that is very important for carrying out heavy activities, especially jumping movements because it can determine how high a volleyball athlete can jump. The study aims to determine the Effect of Leg Muscle Explosive Power Training on the Accuracy of Volleyball Smashes in SSC Unpatti Volleyball Athletes. This study is an experimentl study with a sample of 30 female SSC volleyball athletes. the results of the study were then processed statistically using the t test described For a significant level of 5%, the t table value is known = 6.613. While 1% is known, the t table value = 3.012. That means both the significant level of 5% and 1% value (5%) t table <t count> t table = (1%) or in other words it can be concluded that 2.160 <6.613> 3.012. The effect of explosive power training of leg muscles with knee tuck jump, vertical jump, squat jump, split squat jump exercises shows real effectiveness in the sense that it can be relied on as training for smash accuracy in female volleyball athletes of SSC Unpatti.